CODE-SWITCHING AND CODE-MIXING USED BY INDONESIAN EFL STUDENTS ACROSS DIFFERENT AGES - Putri, Elsa Desi; Cahyono, Bambang Yudi; Zubaidi, Nanang; Anugerahwati, Mirjam (Jurnal Visi Ilmu Pendidikan, 2025)
The phenomena of code-switching and code-mixing were inevitably in EFL classroom. Several studies have been conducted to investigate those issues, meanwhile this research was significant to seek for the kind of code-switching and code-mixing used by EFL students across different age and how this affected their English proficiency level. Therefore, a descriptive-qualitative study through observation was conducted to investigate what kinds of code-switching and code-mixing used. The observation was conducted during the online classes by analysing the recording utterances used by the three EFL students with different age and background. Then, it was found that the code-switching and code-mixing used by the students were varied, such as code-mixing in the form of word, inter-sentential code-switching, and intra-sentential code-switching. Indeed, the kind of code-switching and code-mixing used by the students would show their English proficiency level